Genre Features of the Spanish Language - Artikova, Mahfuza (The Lingua Spectrum, 2025)
This study explores how genre conventions govern pragmatic choices in modern Spanish. Building on corpus-driven data and intercultural research, it analyses discourse markers, politeness strategies and speech-act realisations in academic, business and informal interaction, comparing Peninsular and Latin-American varieties and contrasting native usage with that of Uzbek learners. By integrating internationally recognised scholarship (e.g., Escandell-Vidal; Briz & Grupo Val.Es.Co) with Uzbek-language contributions published in The Lingua Spectrum, the article identifies systematic pragmalinguistic gaps and proposes pedagogical remedies for Spanish instruction in Uzbekistan. Methodologically, a mixed qualitative–quantitative corpus approach is employed, offering an up-to-date picture of genre-bound communication patterns and their intercultural implications.